1983
DOI: 10.3109/01902148309055012
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Lipid Droplets in Fibroblasts of the Hamster Lung by a Diet High in Vitamin A

Abstract: To investigate the effect of vitamin A on the occurrence of lipid droplets in alveolar fibroblasts, light and electron microscopic studies were carried out on the lungs of Syrian golden hamsters fed on diets with a low, normal, or high vitamin A content for a period of 17 weeks. The feeding of the high vitamin A diet resulted in a considerable increase in size and number of lipid droplets in alveolar fibroblasts. These droplets also occurred in fibroblasts of the visceral pleura, and in fibroblasts of connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For example, in vitro lipofibroblasts were shown to repair elastic fibers after treatment of an elastic fiber matrix with elastase (30). Furthermore, vitamin A is stored in lipofibroblasts (37,48) and increases the lipid content of lipofibroblasts in the adult hamster lung (48). As the treatment of emphysematous mice with vitamin A/retinoids resulted in reverse remodeling and the alleviation of the emphysema phenotype (27,19), considerable hopes for the translation of this treatment to patients with emphysema were raised although the regenerative potential of vitamin A/retinoic acid seems to depend on the type of emphysema mouse model or the pharmacogenetics of the mouse strains being used (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in vitro lipofibroblasts were shown to repair elastic fibers after treatment of an elastic fiber matrix with elastase (30). Furthermore, vitamin A is stored in lipofibroblasts (37,48) and increases the lipid content of lipofibroblasts in the adult hamster lung (48). As the treatment of emphysematous mice with vitamin A/retinoids resulted in reverse remodeling and the alleviation of the emphysema phenotype (27,19), considerable hopes for the translation of this treatment to patients with emphysema were raised although the regenerative potential of vitamin A/retinoic acid seems to depend on the type of emphysema mouse model or the pharmacogenetics of the mouse strains being used (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that lipofibroblasts may transfer neutral lipids to Type II cells to support surfactant and phospholipid synthesis (S. E. McGowan & Torday, 1997). The size of lipofibroblasts can be increased by vitamin A feeding suggesting that they are a significant storage site for retinoids in the lung (Okabe, Yorifuji, Yamada, & Takaku, 1984;Spit, 1983). Whereas α-SMA expression has been widely used to identify myofibroblasts, it has recently been shown that Tcf21 expression may identify the lipofibroblast lineage (distinct from myofibroblasts, interstitial fibroblasts, or adventitial fibroblasts) (Park et al, 2019).…”
Section: Role Of Atra In Pulmonary Fibrosismentioning
confidence: 99%
“…Additionally, lipofibroblasts can be found in primary septa of the alveoli, at the very base where secondary septa later grow outward (15, 16). Neonatal lipofibroblasts have been likened to the contractile interstitial cell (CIC), which has been described in the adult lung, based on their contractile phenotype (1,63,117). Although originally researchers reported that LIC were not able to differentiate into NLIC and vice versa (15), CICs are considered to be the progenitor cells of myofibroblasts (1).…”
Section: Fig 2 the Paracrine Effects Of Mesenchymal Stromal Cells (mentioning
confidence: 99%